Is Health Insurance Associated with Health Service Utilization and Economic Burden of Non-Communicable Diseases on Households in Vietnam? - Nguyen Hoang Giang; Tran Thi Mai Oanh; Khuong Anh Tuan; Phan Hong Van; Rohan Jayasuriya (Taylor & Francis Group, 2020)
The rising burden of Non-Communicable Diseases (NCDs) in developing countries has caused high out-of-pocket (OOP) health spending leading to many households suffering Catastrophic Health Expenditure (CHE). This study examined the association between health insurance (HI) on health-care utilization and the burden of OOP expenditure among people with reported NCDs and on their households in Vietnam. The study draws on a cross-sectional household survey of accessibility and utilization of health services in Vietnam. Data were obtained from three provinces to represent urban, rural and mountainous areas of the country. The study used a sample of 2,038 individuals with reported NCD aged over 18 years from 1,642 households having at least one person with reported NCD. The results show that people with reported NCD who had HI were twice as likely to use outpatient care compared with those without HI. Having more than one member with reported NCD resulted in double the odds of a household suffering CHE. Households in the three lowest wealth quintiles were more likely to encounter CHE and financial distress than economically better-off households. HI did not provide a protective effect to households, as there was no significant association between the HI status of household members with reported NCD and CHE or financial distress. Seeking care at higher-level facilities was significantly associated with CHE. This study highlights the need for evidence to design future HI-based interventions targeting susceptible populations to narrow the gaps in health service utilization among the population and mitigate financial catastrophe associated with NCDs. Abbreviations: NCD: Noncommunicable diseases; UHC: Universal Health Coverage; HI: Health insurance; CHE: Catastrophic health expenditure; OOP: Out of Pocket